2023
DOI: 10.1101/2023.07.24.23293082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-Year Follow-up of Young People with ME/CFS Following Infectious Mononucleosis by Epstein-Barr Virus

Rafael Pricoco,
Paulina Meidel,
Tim Hofberger
et al.

Abstract: Background: Infectious mononucleosis, caused by the Epstein-Barr Virus (EBV-IM), has been linked to the development of myalgic encephalomyelitis/chronic fatigue-syndrome (ME/CFS) in children, adolescents, and young adults. Our study presents the first cohort of young individuals in Germany who were diagnosed with ME/CFS following EBV-IM. Methods: We conducted a one-year follow-up of 25 young people diagnosed with ME/CFS at our specialized tertiary outpatient service by clinical criteria requiring post-exertion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…The physical and social functioning of MECFS-R participants was severely reduced as indicated by low Bell and SF-36 scores, while higher scores were found for emotional role functioning and psychological well-being [70,71]. This aligns with earlier reports indicating that the HRQoL of patients with ME/CFS compared to other chronic diseases is severely compromised, mainly due to physical impairment [55,56,68,72] Moreover, in support of published results [73], MECFS-R participants suffered from significant autonomic dysfunction as indicated by high COMPASS-31 scores. We recommend the Bell score, SF-36, and COMPASS-31 as standard measures for clinical phenotyping to facilitate both local medical care as well as future studies with secondary use of MECFS-R data.…”
Section: Clinical Characterization Of Pilot Study Participantssupporting
confidence: 81%
See 1 more Smart Citation
“…The physical and social functioning of MECFS-R participants was severely reduced as indicated by low Bell and SF-36 scores, while higher scores were found for emotional role functioning and psychological well-being [70,71]. This aligns with earlier reports indicating that the HRQoL of patients with ME/CFS compared to other chronic diseases is severely compromised, mainly due to physical impairment [55,56,68,72] Moreover, in support of published results [73], MECFS-R participants suffered from significant autonomic dysfunction as indicated by high COMPASS-31 scores. We recommend the Bell score, SF-36, and COMPASS-31 as standard measures for clinical phenotyping to facilitate both local medical care as well as future studies with secondary use of MECFS-R data.…”
Section: Clinical Characterization Of Pilot Study Participantssupporting
confidence: 81%
“…Accordingly, a predominance of SARS-CoV-2 was identified in adults (59.5%) and EBV in pediatric patients (26%) in our first cohort. Non-infectious triggers are most likely underrepresented since both recruiting centers are focusing on post-infectious ME/CFS as immunological departments [55,56,68]. However, the registry allows a very precise documentation of triggering events including clinical and laboratory data from the time of initial symptoms, and therefore facilitates a stratification of study participants along confirmed versus probable and selfreported triggers.…”
Section: Clinical Characterization Of Pilot Study Participantsmentioning
confidence: 99%